2009
DOI: 10.1016/j.jeconbus.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two audiences: Spectators, television viewers and outcome uncertainty in Spanish football

Abstract: This paper tests for the impact of match outcome uncertainty on two types of audience for Spanish football, fans at the stadium and television viewers. We find that fans inside the stadium prefer games that are less and not more likely to finish with a close score. This is contrary to much theoretical literature in sports economics which argues that fans prefer close contests and imposes this assumption in formal modelling. We also find that television viewers prefer close contests to more predictable contests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
106
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 24 publications
6
106
0
3
Order By: Relevance
“…Buraimo and Simmons (2008) modeled English Premier League attendance and concluded that attendance is minimized if home win probability derived from betting odds equals about 0.35. Buraimo and Simmons (2009) obtained a similar result for Spanish soccer. However, Benz et al (2009) found that for one model specification, German Bundesliga attendance (excluding season tickets) was maximized for home team win probability equal to 0.53.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Buraimo and Simmons (2008) modeled English Premier League attendance and concluded that attendance is minimized if home win probability derived from betting odds equals about 0.35. Buraimo and Simmons (2009) obtained a similar result for Spanish soccer. However, Benz et al (2009) found that for one model specification, German Bundesliga attendance (excluding season tickets) was maximized for home team win probability equal to 0.53.…”
Section: Introductionsupporting
confidence: 62%
“…Some authors address this by taking the estimated attendance demand function and asking what would happen if the league structure changed (Dobson et al, 2001) or if teams were more evenly balanced (Forrest and Simmons, 2002;Buraimo and Simmons, 2009). However, if the estimated demand function is misspecified, this approach could still lead to incorrect conclusions.…”
Section: The Problem With Regressionmentioning
confidence: 99%
“…Despite the hypothesis that match attendance boosts excitement for television viewers, Buraimo (2008) finds that match attendance is negatively related to the televising of matches. Buraimo and Simmons (2009) also test the impact of outcome uncertainty on fan interest (i.e., consumer demand) for both fans in attendance and television audiences.…”
Section: Recent Literature On Fan Interest and Outcome Uncertaintymentioning
confidence: 99%
“…It is the most frequently transmitted sport by the commercial sports TV channels (Jeanrenaud & Kesenne, 2006). From the statistics of these companies, we can deduce that these programs are between the most viewed ones (Buraimo & Simmons, 2009). …”
Section: Introductionmentioning
confidence: 99%